Alterations in multipotent mesenchymal stromal cells from the bone marrow of acute myeloid leukemia patients at diagnosis and during treatment. Issue 8 (3rd July 2019) - Shipounova, Irina N.; Petinati, Nataliya A.; Bigildeev, Alexey E.; Sorokina, Tamara V.; Kuzmina, Larisa A.; Parovichnikova, Elena N.; Savchenko, Valery G.
Abstract: We analyzed multipotent mesenchymal stromal cells (MMSCs) from the bone marrow (BM) of 33 acute myeloid leukemia (AML) patients at diagnosis, after the first course of chemotherapy (day 37), and at days 100 and 180 after diagnosis. All patients were treated according to the AML 01.10 protocol. Cumulative production of MMSCs from AML patients at diagnosis was normal but increased during treatment. Most of the studied genes were upregulated at AML diagnosis, some ( IL6, IL1B, LIF ) remained upregulated during treatment, and others were downregulated ( FGFR1, ICAM1 ) or normalized. A few genes were normal at diagnosis but decreased during treatment ( FGF2, FGFR2, VEGF, SDF1, SOX9, TGFB1 ). The upregulation of proinflammatory genes both at diagnosis and during remission reflects ongoing inflammation. PDGFRB expression was upregulated in MMSCs from patients in relapse versus those in remission. The AML 01.10 protocol downregulates the expression of genes related to proliferation, differentiation and niche formation.